EFFECTS OF ANTHROPOMETRIC VARIABLES ON SPORT PERFORMANCE OF MALE UNIVERSITY CHAMPION-HANDBALLERS IN WEST AFRICA (NIGERIA) - Surajudeen Tosho (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2020)
This study focused on the effects of anthropometric variables on male handball champions in West Africa. An ex-post facto research design was adopted. The population of all male handball players in the West African University Games (University of Ilorin; University of Ghana and University of Abomey-Calavi) were participants in the study. Two research instruments were adopted in this study this includes measuring tape and a standard handball court. Census sampling technique was used to select all 37 players available during the contest. Census method is the method of statistical enumeration where all members of the population are studied . These players composed of (Wrist (cm) 18.88, Chest (cm) 17.78, mid-thigh(cm) 18.35, Wrist (cm) 91.96, Chest (cm) 95.02, mid-thigh 89.83, Wrist (cm) 49.37, mid-thigh 55.04, Wrist (cm) 49.26). To test a substantive difference between the groups determined at 0.05alpha significant levels, descriptive and inferential statistics for t test and ANOVA Scheffe post hoc, multiple comparison tests were adopted. The results of this study showed that men players had considerable differences in anthropometric measurements. As the men's players were significantly different in the handle circumference (f=4.624>3.32 (0.05) df36); chest circumference (f=.750<3.32(0.05) df36). Coaches were recommended to focus on these variables in selecting and coaching processes (Wrist circumference, Chest curvature, Thigh). This study also recommends that this profiling should be adopted in players’ selection and the development of sport specific programs. Key words: Anthropometric, Performance, Wrist girth.